A totally recombinant fibrin matrix for mesenchymal stem cell culture and delivery. Issue 12 (27th August 2018) - Wang, Ou; Ismail, Ayman; Fabian, Frank Marco; Lin, Haishuang; Li, Qiang; Elowsky, Christian; Carlson, Mark A.; Burgess, Wilson; Velander, William H.; Kidambi, Srivatsan; Lei, Yuguo
Abstract: Mesenchymal stem cells (MSCs) have been widely studied for tissue engineering and treating diseases in laboratories, clinical trials, and clinics. Fibrin matrices are often used to culture MSCs or increase the retention of MSCs at the injection site. However, fibrins made with the human plasma derived fibrinogen have high cost and risk of human pathogen transmission. In this article, we studied if fibrin matrices made with recombinant human fibrinogen, recombinant human thrombin, and recombinant human factor XIII could be used to culture and deliver MSCs. We systematically investigated the relationships between the fibrin matrix formulation, its nanostructure, and the behaviors of the cells in the matrix including the cell morphology, viability, and growth. We found that the fibrinogen concentration significantly affected the matrix structure and cell behaviors. We then used an optimized fibrin matrix to deliver human MSCs into mice subcutaneously. We found that the matrix could significantly enhance the retention of MSCs at the injection site. To our best knowledge, this is the first study on using fibrin matrices made with entirely recombinant proteins for culturing and delivering MSCs. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 3135–3142, 2018.